Organizational Climate Management in the Context of Initial Mathematics Teacher Education - Emilio Sagredo-Lillo; Jorge L. Zapata; Yocelyn Parra-Urrea; Exequiel Llanos-Lagos (Emerging Science Journal, 2024)
Objective: This study aims to analyze the impact of organizational management on motivation, satisfaction and commitment in teacher training in the context of Chilean quality assurance policies that emphasize a positive school climate and good coexistence. Methods: Using a Likert scale with a Cronbach's alpha of 0.957, we surveyed 62 students in a mathematics teacher education program. A multiple linear regression analysis was conducted to examine how motivation, satisfaction, and engagement were related to organizational management and climate. Findings: The results show that motivation and satisfaction are significant predictors, explaining 61.5% of the variance in organizational management, while commitment also influences climate, but to a lesser extent. These results underscore the importance of motivation and satisfaction for effective organizational management and suggest that these factors may be more important than commitment in shaping a positive organizational climate. Novelty/Improvement:This study contributes to the literature by highlighting the need for management models that are tailored to specific educational contexts and calls for future research to examine additional variables that influence organizational climate in higher education to improve our understanding of the factors that influence educational environments. Doi: 10.28991/ESJ-2024-SIED1-018 Full Text: PDF